2008
DOI: 10.1186/1472-6963-8-202
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to accessing TB diagnosis for rural-to-urban migrants with chronic cough in Chongqing, China: A mixed methods study

Abstract: Background: China is facing a significant tuberculosis epidemic among rural-to-urban migrants, which poses a threat to TB control. This study aimed to understand the health seeking behaviour of and health systems responses to migrants and permanent urban residents suffering from chronic cough, in order to identify the factors influencing delays for both groups in receiving a TB diagnosis in urban China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 22 publications
7
92
1
1
Order By: Relevance
“…In addition to economic status, several quantitative studies in China have reported that other barriers to access to TB care among migrant patients are lack of awareness and lack of knowledge in a marginalized population and inadequate and complicated referral to TB dispensaries (23,32). A large proportion of migrant TB patients tend to first visit a non-hospital facility for treatment of their symptoms, where doctors are more likely to delay due to a lack of skill and experience in identifying potential TB and where the facility has a financial incentive to keep patients at the facility (33).…”
Section: Barriers To Tb Detection and Treatment For The Migrant Populmentioning
confidence: 99%
“…In addition to economic status, several quantitative studies in China have reported that other barriers to access to TB care among migrant patients are lack of awareness and lack of knowledge in a marginalized population and inadequate and complicated referral to TB dispensaries (23,32). A large proportion of migrant TB patients tend to first visit a non-hospital facility for treatment of their symptoms, where doctors are more likely to delay due to a lack of skill and experience in identifying potential TB and where the facility has a financial incentive to keep patients at the facility (33).…”
Section: Barriers To Tb Detection and Treatment For The Migrant Populmentioning
confidence: 99%
“…For example, migrant workers constitute a large proportion of TB patients in some cities in China and they are often hard to trace during evaluation or after treatment is initiated. 15,16 Additionally, public hospital settings have been criticized previously for inadequate TB treatment, leading to drug resistance. 13,14 We aimed to investigate specific health-care-based locations that TB patients visit prior to diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…This is specifically due to the fact that patients usually resort to institutions or facilities that lack proper arrangement for TB diagnosis such as pharmacies and informal health care settings. The lack of knowledge coupled with poor financial capacity to pay for the diagnosis [4] especially in rural population prevents them from being diagnosed properly as well.…”
Section: Mbbs Universal College Medical Sciences Nepalmentioning
confidence: 99%
“…There is problem in understanding of the regimens and being complaint to the services provided [10] that also reflects the provider-patient relation as one of the important factors in treatment. Patients find it difficult in seeking T.B treatment as they don't trust the program and most of them don't possess enough knowledge about the disease itself [4]. In addition, the policies regarding the adoption of treatment should be contextual [11].…”
Section: Mbbs Universal College Medical Sciences Nepalmentioning
confidence: 99%
See 1 more Smart Citation